Electronics for kids : play with simple circuits and experiment with electricity! - Nydal Dahl, Øyvind (No Starch Press, 2016)
"Demystifies electricity and teaches how to build electronics projects. Covers how circuits, voltage, and current work. Each part of the book focuses on different fundamental electronics concepts with hands-on projects"--